Hyper-Immunoglobulin E Syndrome in a Neonate: A Case Report (Global Journal of Medical Research, 2014)
Hyper-immunoglobulin E syndrome (Job syndrome) is a rare primary immunod- eficiency with variable presentation, characterized by recurrent infections, facial dimorphism, eczema, scoliosis, joint hyper-extensibility, pathologic fractures, very high IgE (>2000 IU/mL), severe eosinophilia and variable impaired T cell function. We present a case of Hyperimmunoglobulin E syndrome in neonate with review of the literature.
Keywords: hyper-immunoglobulin E syndrome; recurrent infections; neonate